Working Capital Requirements in Indonesia: Determining Factors, Adjustment Speed, and Financial Constraints - Lukas Purwoto (Jurnal ASET (Akuntansi Riset), 2021)
Working capital behavior has attracted the attention of researchers in relation to company development and the financial environment. This study aims to investigate the determinants and speed of target adjustment of working capital requirements and to examine whether financial constraints lead to differences in target adjustment behavior. The sample consists of public companies in Indonesia for the 2011-2018 period. The results show that sales growth, leverage, size, operating cash flow, age, and fixed assets have a significant effect on working capital requirements. By applying the GMM system from the dynamic panel model, this study also demonstrates that companies have a target level of working capital. Moreover, this study shows that companies that do not experience financial constraints make adjustments to the target, but this does not happen to companies that experience financial constraints. The adjustment behavior of optimal working capital is highly dependent on the company's financial constraints.